Experimental investigation of the air flow in a simplified underhood environment. (September 2022) - Franzke, Randi; Sebben, Simone; Willeson, Emil
In this paper, a simplified underhood environment is proposed to investigate the air flow distribution in a vehicle-like set-up and provide high quality measurement data that can be used for the validation of Computational Fluid Dynamic methods. The rig can be equipped with two types of front openings representative for electrified vehicles. Furthermore, it is possible to install differently shaped blockages downstream of the fan to imitate large underhood components. The distance between the blockages and the fan can be varied in longitudinal and lateral direction. The measurements are performed with Laser Doppler Anemometry at a fixed distance downstream of the fan. The results show that the lack of an upper grille opening in the configuration for a battery electric vehicle has a notable impact on the flow field in the reference case without any downstream blockage. However, the differences in the flow field between the two front designs become less when a downstream obstruction is present. The longitudinal and lateral position of the blockages have a minor impact on the flow field compared to the shape of the obstacle itself.